Analysis of linear motor with symmetrical EMF vector for household elevator application - Nor Aishah Md Zuki; Raja Nor Firdaus Kashfi Raja Othman; Fairul Azhar Abdul Shukor; Suhairi Rizuan Che Ahmad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Linear permanent magnet synchronous motor (LPMSM) has emerged as a viable alternative to other linear motors for higher thrust lifting action. With the advancement of permanent magnets, LPMSM could contribute to energy conversation while also being suitable for applications requiring higher thrust, such as elevator. However, because the existing LPMSM is larger in size, it requires more space to be equipped with a household elevator. To address this issue, a new LPMSM with increased thrust capability has been proposed. The new LPMSM is modelled and analyzed in terms of back EMF and force in this paper. For improved performance, a symmetrical EMF vector is applied to the new LPMSM. In terms of back EMF and force, 4 LPMSM models are studied. According to the results, 6 slot 4 pole has the highest back EMF when compared to the others. As a suitable combination of slot and pole, a symmetrical EMF vector is the suggested LPMSM at the end of this research.